Impacts of environmental tobacco smoke on the onset and progression of multiple sclerosis: a systematic review - Marco Antônio Machado Schlindwein; Marcelo Henrique de Moura Campos; Leticia Caroline Breis; Beatriz Sordi Chara; Clara Sasse Scherer; Vitória Augusta Piva Caminski; André Matta; Marcus Vinicius Magno Gonçalves (Arquivos de Neuro-Psiquiatria)
Background Unlike cigarette smoking, environmental tobacco smoke (ETS) has not been as well described as an environmental risk for Multiple sclerosis (MS) nor as a risk factor for disease progression.